Speaking of corporate social responsibility - LIANG, Hao (Institutional Knowledge at Singapore Management University, 2014)
We argue that the language spoken by corporate decision makers influences their firms’ social responsibility and sustainability practices. Linguists suggest that obligatory future-time-reference (FTR) in a language reduces the psychological importance of the future. Prior research has shown that speakers of strong FTR languages (such as English, French, and Spanish) exhibit less future-oriented behavior (Chen, 2013). Yet, research has not established how this mechanism may affect the future-oriented activities of corporations. We theorize that companies with strong-FTR languages as their official/working language would have less of a future orientation and so perform worse in future-oriented activities such as corporate social responsibility (CSR) compared to those in weak-FTR language environments. Examining thousands of global companies across 59 countries from 1999-2011, we find support for our theory, and further that the negative association between FTR and CSR performance is weaker for firms that have greater exposure to diverse global languages as a result of (a) being headquartered in countries with higher degree of globalization, (b) having a higher degree of internationalization, and (c) having a CEO with more international experience. Our results suggest that language use by corporations is a key cultural variable that is a strong predictor of CSR and sustainability.